2004
DOI: 10.1016/j.ijgo.2003.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy index in the preoperative evaluation of pelvic masses

Abstract: The RMI is able to correctly discriminate between malignant and benign pelvic masses. It is a simple scoring system that can be introduced easily into clinical practice to facilitate the selection of patients who would benefit from primary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 15 publications
8
45
1
1
Order By: Relevance
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In our study we found sensitivity 73.5%, specificity 97.1%, PPV 95.3% and NPV 82% by using RMI of more than 200. In the literature different values were defined for RMI and our results confirmed these studies (Jacobs et al, 1990;Davies et al, 1993;Tingulstad et al, 1999;Manjunath et al, 2001;Anderson et al, 2003;Ma et al, 2003;Obeidat et al, 2004;Yamamoto et al, 2009;Van der Akker et al, 2010;Ashrafgangooei et al, 2011;Van Gorp et al, 2012;Sayasneh et al, 2013;Terzic et al, 2013;Arun-Muthuvel et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Yamamoto et al [12], who created their own model of a malignancy risk index, added the parameter of tumor size (S) to the RMI, and have termed it RMI 4. Retrospective and prospective validation of the four versions of the RMI have been conducted in different clinical studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], where a cutoff value of 200 for RMI 1-3 and 450 for RMI 4 showed the best discrimination between benign and malignant pelvic masses, with high levels of sensitivity and specificity (sensitivity 51%-90%, specificity 51%-97%). The main advantage of four RMIs is that it is a simple scoring system that can be applied directly into clinical practice without the introduction of expensive or complicated methods (such as computed tomography scan, magnetic resonance imaging, and wholebody positron emission tomography).…”
Section: Jung-woo Park Et Al Four Rmis In Pelvic Massesmentioning
confidence: 99%
“…Other models have been constructed by other researchers with different predicting accuracy namely Risk of Malignancy Index (RMI) number 1-5 based on sonographic findings, menopausal status and CA125 level (Soegaard, 2003;Obeidat, 2004;Leelahakorn, 2005;Ulusoy, 2007;Moolthiya, 2009).…”
Section: Introductionmentioning
confidence: 99%